The Impact of Coagulant Type and Dosage on Turbidity and pH Levels in Raw Water Treatment: A Comparative Study Using The Jar Test Method and Full-Scale Water Treatment Plant - Wijaya, Budi; Sudarno, Sudarno; Samudro, Ganjar; Ardhianto, Rachmad (Elkawnie, 2025)
Abstract: The Gajah Mungkur Multipurpose Dam in Wonogiri functions as a source of raw surface water for the surrounding area. This water often contains suspended particles and colloidal substances due to natural processes such as soil erosion, plant decomposition, and microbial activity. This study evaluated three coagulants: Hincolac, PAC 280 Ac, and PAC 250 Ac, at dosages of 60, 70, 80, 90, and 100 ppm. The results of the jar test were compared with those of the full-scale water treatment plant operational test. The findings revealed that the Hincolac coagulant demonstrated superior performance, achieving an efficiency level of 98.60%, which exceeded that of the PAC 250 A and 280 AC coagulants. Hincolac coagulant reached optimal effectiveness at a concentration of 80 ppm, whereas PAC 280 AC and 250 coagulants achieved their highest efficiency at 100 ppm, resulting in turbidity reductions of 98.1% and 97.92%, respectively. Statistical analysis showed that all coagulant types significantly affected turbidity, pH, and floc size (p < 0.001). In a comprehensive application, a dosage of Hincolac 67 ± 7.7 ppm was comparable to the tube test method and effectively achieved a 99% reduction in turbidity in the water-treatment output. Elevated alkalinity and Al₂O₃ concentrations significantly influence the effectiveness of coagulant-based water treatment. Abstrak: Bendungan Serbaguna Gajah Mungkur di Wonogiri berfungsi sebagai sumber air baku berbasis air permukaan. Air permukaan sering kali mengandung partikel tersuspensi dan bahan koloid yang dihasilkan dari kejadian alami, seperti erosi tanah, pembusukan tanaman, dan aktivitas mikroba. Studi ini melibatkan tiga jenis koagulan, yaitu Hincolac, PAC 280 Ac, dan PAC 250 Ac, dan menggunakan metode dosis variabel, 60, 70, 80, 90, dan 100 (ppm). Hasil uji jar  test dibandingkan dengan hasil uji operasional wtp kapasitas penuh. Hasil studi menunjukkan bahwa koagulan Hincolac menunjukkan kinerja yang lebih baik, mencapai tingkat efisiensi yang tinggi sebesar 98,60% lebih baik dari pada koagulan jenis PAC 250 A dan 280 AC. Koagulan Hincolac mencapai efisiensi tertinggi pada konsentrasi 80 ppm, dibandingkan dengan koagulan PAC 280 AC dan 250 yang dicapai pada konsentrasi 100 ppm, menghasilkan pengurangan kekeruhan 98,1% dan 97,92%. Analisis statistik menunjukkan bahwa semua jenis koagulan memiliki dampak yang signifikan terhadap kekeruhan, pH, dan ukuran flok, dengan nilai p <0,001. Dalam aplikasi skala penuh, dosis Hincolac 67 ± 7,7 ppm sebanding dengan metode uji tabung, dan berhasil mencapai pengurangan kekeruhan 99% pada output pengolahan air. Tingkat kebasaan dan konsentrasi Al2O3 yang tinggi memiliki dampak yang signifikan terhadap hasil akhir pengolahan air berbasis koagulan.